2012
DOI: 10.1038/hr.2012.145
|View full text |Cite
|
Sign up to set email alerts
|

Impact of visit-to-visit variability of blood pressure on deterioration of renal function in patients with non-diabetic chronic kidney disease

Abstract: An association between visit-to-visit variability (VVV) of blood pressure (BP) and renal damage was recently reported in a cross-sectional study. We aimed to clarify the longitudinal effect of VVV of BP on deterioration of renal function in patients with non-diabetic chronic kidney disease (CKD). We retrospectively studied 56 patients with non-diabetic CKD (stage 3 or 4) who visited our nephrology clinic between September 1994 and May 2011. VVV of BP was defined as the standard deviation and coefficient of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 59 publications
3
52
3
2
Order By: Relevance
“…Similarly, Yokota et al 16 reported that visit-to-visit BPV correlated significantly with the annual decline of eGFR in patients with non-diabetic CKD. Our data are in accordance with these findings as we showed indices of visit-to-visit BPV correlated negatively with eGFR, independent of age, HbA1c, LDL cholesterol, uric acid and M SBP in patients with CKD (Table 3).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Similarly, Yokota et al 16 reported that visit-to-visit BPV correlated significantly with the annual decline of eGFR in patients with non-diabetic CKD. Our data are in accordance with these findings as we showed indices of visit-to-visit BPV correlated negatively with eGFR, independent of age, HbA1c, LDL cholesterol, uric acid and M SBP in patients with CKD (Table 3).…”
Section: Discussionmentioning
confidence: 86%
“…High visit-to-visit BPV [14][15][16] and endothelial dysfunction 17 have been reported in CKD patients. This suggests that there may be an association between these two factors in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…In some but not all studies, persons with higher BP variability had more rapid CKD progression as measured by declines in eGFR or increases in urinary albumin (9)(10)(11)(12)(13). Some studies of persons with diabetes have shown an association of BP variability with more clinically impactful renal outcomes, including ESRD (10,14), but such an association has not been shown among persons without diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…To calculate VVV of BP, we used data from seven followup visits that occurred 6,9,12,16,20,24, and 28 months after randomization. We started at the 6-month follow-up visit to avoid potential confounding by BP changes that occurred between randomization and that visit (mean BP fell by approximately 8/5 mmHg).…”
Section: Study Visits Bp Measurements and Calculation Of Vvv Of Bpmentioning
confidence: 99%
“…Yokota et al reported that visit-to-visit BP variability was associated with renal function decline in nondiabetic chronic kidney disease (21). Therefore, the aim of the present study was to investigate the relationships between visit-to-visit BP variability, RRF, and cardiovascular status in continuous ambulatory PD (CAPD) patients.…”
Section: Introductionmentioning
confidence: 99%